Tourism Village Development as a Grassroots Indicator of Maritime Development: A Qualitative Case Study of a Coastal Community in Southeast Sulawesi, Indonesia - Adrian Tawai; Muhammad Yusuf; Taufik Taufik; Muhammad Ilham Nur Ikhsan Rintaka (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2025)
Indonesia’s maritime development agenda emphasizes the integration of economic growth, community empowerment, and sustainability in coastal and archipelagic regions. Among various development instruments, tourism villages—particularly those based on marine and coastal resources—have gained increasing attention as vehicles for community-based development. However, existing studies largely position tourism villages as development outcomes, with limited attention to their potential role as analytical indicators of maritime development at the local level. This study aims to examine tourism village development as a grassroots indicator of maritime development through a qualitative case study in Kelurahan Toronipa, Southeast Sulawesi. Employing a qualitative case study approach, data were collected through semi-structured interviews with key stakeholders, non-participant observation, and document analysis. The data were analyzed using thematic analysis to identify patterns related to community participation, governance, socio-economic transformation, infrastructure development, and sustainability practices. The findings reveal that tourism village development in Toronipa reflects broader maritime development processes by facilitating livelihood diversification, strengthening community participation in governance, improving infrastructure accessibility, and integrating maritime cultural values into tourism activities. At the same time, the study identifies challenges related to uneven participation, environmental management, and the potential displacement of traditional maritime livelihoods. This research contributes theoretically by repositioning tourism villages as socio-economic and governance indicators of maritime development rather than merely policy outcomes. Practically, the findings suggest that tourism village performance can inform more inclusive and context-sensitive maritime development policies, particularly in coastal regions of eastern Indonesia. The study highlights the importance of integrating community empowerment, governance quality, and sustainability considerations into the assessment of maritime development at the grassroots level.